LASER 40AR/39AR AGES OF SINGLE DETRITAL WHITE MICA GRAINS RELATED TO THE EXHUMATION OF NEOPROTEROZOIC AND LATE DEVONIAN HIGH PRESSURE ROCKS IN THE SOUTHERN URALS (RUSSIA) - Willner A.P.; Wartho J.-A.; Kramm U.; Puchkov V.N. (My University, 2004)
Single grains of detrital white mica from two different synorogenic sediments in the Southern Urals were analysed using the insitu ultraviolet laser ablation Ar609 Ma age group is phengitic in composition (Si 3.3732 Ma age group is comprised of muscovite composition grains only. The first group is compatible with the time of late exhumation and emplacement of a source area containing high-pressure rocks, the Neoproterozoic Beloretzk terrane. The older age range is compatible with a long history of cooling and the allochthonous nature of this terrane. Detrital white mica from the Famennian sandstones (Zilair Formation) comprises one age group (3423.39 per formula unit) and muscovite, and a second group (446continent collision.
Keywords: Devonian; Neoproterozoic; Paleozoic::Devonian; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская; Палеозой::Девонская